2004
DOI: 10.1007/s11051-004-2162-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle production by UV irradiation of combustion generated soot particles

Abstract: Laser ablation of surfaces normally produce high temperature plasmas that are difficult to control. By irradiating small particles in the gas phase, we can better control the size and concentration of the resulting particles when different materials are photofragmented. Here, we irradiate soot with 193 nm light from an ArF excimer laser. Irradiating the original agglomerated particles at fluences ranging from 0.07 to 0.26 J/cm 2 with repetition rates of 20 and 100 Hz produces a large number of small, unagglome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 21 publications
4
29
0
Order By: Relevance
“…When these results are compared with our previous results of soot 20 and NaCl 19 particles irradiated at 193 nm, similarities and differences are observed. The nonirradiated soot and NaCl particles have agglomerated structures composed of ∼40 nm spherical primary particles with a fractal dimension (D f ) of approximately 1.8 and log-normal size distributions with mean diameters of 265 and 120 nm, respectively.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…When these results are compared with our previous results of soot 20 and NaCl 19 particles irradiated at 193 nm, similarities and differences are observed. The nonirradiated soot and NaCl particles have agglomerated structures composed of ∼40 nm spherical primary particles with a fractal dimension (D f ) of approximately 1.8 and log-normal size distributions with mean diameters of 265 and 120 nm, respectively.…”
Section: Discussionsupporting
confidence: 66%
“…While we observed atomic and molecular fluorescence using 193 nm light, neither incandescence nor plasma formation was seen from the different particles (polystyrene, soot, and NaCl). [18][19][20][21] However, when we replaced the 193 nm laser with a frequency-doubled Nd:YAG laser at 532 nm, long lifetime broadband incandescence was observed from the same particles at similar fluences. Unlike nanosecond laser irradiation at longer wavelengths, thermal effects are negligible in 193 nm laser photochemistry of polymer surfaces, and the thermal effects increase with the incident wavelength.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This provided efficient mixing and improved the combustion regime. Stipe et al (2004) suggested that UV photo fragmentation can be effective in controlling particle size and morphology, and can be a useful diagnostic for studying elements of the laser ablation process. propane, and benzene).…”
Section: Concurrent Researchmentioning
confidence: 99%